Structural, morphological and photometric properties of sonochemically synthesized Eu3+ doped Y2O3 nanophosphor for optoelectronic devices. (October 2017) - Venkatachalaiah, K.N.; Nagabhushana, H.; Darshan, G.P.; Basavaraj, R.B.; Prasad, B. Daruka; Sharma, S.C.
Graphical abstract: Highlights: Y2 O3 :Eu 3+ nanophosphors were prepared by modified sonochemical route using A.V. gel. Reported the effects of pH, time and concentration of bio-surfactant on the morphologies. Synthesis route is rapid, bio-compatible, cost-effective useful for industrial application. Photometric properties reveals the use of phosphor for optoelectronics applications. Abstract: Synthesis of Eu 3+ doped Y2 O3 nanophosphors via modified sonochemical method was presented. Morphologies of the prepared products were analyzed with respect to the influential parameters during the preparation time. The photoluminescence (PL) emission spectra exhibits several peaks at ∼537 nm, 598 nm, 613 nm and 662 nm attributed to 5 D0 → 7 FJ ( J = 0, 1–3) transitions of Eu 3+ ions in the host lattice. The types of energy transfer between the Eu 3+ ions were responsible for concentration quenching confirms the electric dipole–quadrupole interaction among the ions. The Judd-Ofelt intensity parameters and other radiative properties were estimated by using PL emission spectra. The photometric characteristics of the prepared samples indicate that the color co-ordinates were tune towards pure red emission with color purity of ∼88%. The results signified that the prepared Y2 O3 :Eu 3+ was a potential amber phosphor for solid state and LED's applications.